Formation of senior preschoolers’ creative skills through theatrical and speech activities - Kotelianets, Yuliia Serheevna (2021)
This article reveals the role of dramatization in a preschooler’s life. The main types of theatrical activities used in preschool education are highlighted. In the process of our research, we used qualitative methodology. To study the specifics of the impact of different types of the theater on the development of the older preschoolers’ creative skills, testing was conducted, which allowed determining the level of formation of these skills. The test results are processed according to the following indicators of creative skills: lightness, flexibility, originality, elaboration. A formative experiment was conducted, aimed at developing a program that will promote the formation of preschoolers’ creative skills through theatrical and speech activities. For the effective implementation of the tasks, the work on the development of children’s speech abilities using theatrical activities was systematized. In the process of analyzing the indicators of the level of mastering the creative skills before and after the experiment, it was found that the indicators have improved significantly: “low level” after the experiment in one of the groups was eliminated. The results of the experiment suggest that theatrical activities are one of the effective means for the development of preschoolers’ speech abilities.